Absence of human herpesvirus 6B detection in association with illness in children undergoing cancer chemotherapy. Issue 8 (3rd February 2016) - Goldfarb, Johanna; Borges, Nirica; Gowans, Laura K.; Kohn, Debra; Worley, Sarah; Li, Liang; Yen‐Lieberman, Belinda; Lach, Donna; Danziger‐Isakov, Lara; Yee‐Guardino, Stephanie; Trunick, Charles; Pellett, Philip E.
Abstract : The lymphotropic herpesviruses, cytomegalovirus (CMV), Epstein‐Barr virus (EBV), and human herpesvirus 6B (HHV‐6B) can reactivate and cause disease in organ transplant recipients; the contributions of HHV‐6A and HHV‐7 to disease are less certain. Less is known about their pathogenic roles in children undergoing treatment for malignancies. Children with newly diagnosed cancer were followed for 24 months. Clinical information and blood samples were collected during routine visits and during acute visits for fever or possible viral infections. Lymphotropic herpesvirus DNA in blood was measured by polymerase chain reaction (PCR). Although HHV‐6B DNA was detected at least once in about half of the patients; the other viruses were seldom detected. There was no association between HHV‐6B detection and individual acute clinical events, however, HHV‐6B detection was more common in children who experienced more frequent acute clinical events. In children being treated for various malignancies, HHV‐6B detection was common, but was not associated with individual events of acute illness. Thus, if HHV‐6B is not assessed longitudinally, clinical events may be misattributed to the virus. The elevated frequency of detection of HHV‐6B in sicker children is consistent with prior reports of its detection during apparently unrelated acute clinical events. J. Med. Virol. 88:1427–1437, 2016 . © 2016 Wiley Periodicals, Inc.